Uma análise multimodal à luz do modelo GeM: homepages do Ministério da Justiça e do Ministério do Meio Ambiente - Thiago Brazileiro Vilar Hermont (2014)
The present study aims to analyze the homepages from the Ministry of Environment and the Ministry of Justice in Brazil by investigating how language is presented in the aforementioned digital pages. To do so, the investigation relies on the principles of multimodality and social semiotics and, therefore, on the studies carried out by the Systemic-Functional Linguistics Theory, the Grammar of Visual Design and the GeM Model Genre and Multimodality. Whereas the first two theoretical foundations underlie the investigation related to the analyses of the two homepages, the GeM Model introduces a more practical approach towards the documents under examination mainly via its layout and base layers. In this way, the minimal basic and layout units from the homepages are detailed thus highlighting their relation with the notion of multimodality. The research intends to demonstrate which the recurrent elements in the Ministries official pages are, the similarities and differences between such elements, as well as how both the base and the layout structures from the GeM Model contribute to a higher degree of modality in the language used in the governmental sites. Based on the data collected and the analyses carried out, it is possible to determine that the online environments investigated are not only notably characterized by multimodal language but also in accordance with the most recent tendencies regarding social practices and the plurality of semiotic modes. Such features guarantee the Brazilian society adequate access to the official contents issued by the government.